The translation of a film discourse as a special type of audiovisual translation (Eurasian Journal of Philology Science and Education, 2015)
This article is devoted to the discussion of a translation of film discourse in terms of polysemiotic concept. The special emphasis is made on lingua cultural components of a film discourse; due to the fact that in cinema translation two or more cultures meet and when translators translate any material they transfer not only linguistics features, but also cultural aspects of a source nation. The concept a film discourse might be defined through the concept film text. In comparison with a film discourse a film text might be considered as its fragment, whereas a film discourses as a whole text or a corpus of texts combined by some features. In our opinion a film discourse is the reflection of a specific type of culture; reflection of reality and modern understanding of traditional values and forming new values. That is why it is very important to pay attention to national and cultural aspects of a film discourse while transferring them from the source language to the target language.
Keywords: film discourse; cinema; culture; language; translation; audiovisual translatiоn